The global approaches to the regulation of quantum communication - D. A. Kuleshov (Цифровое право, 2024)
In the rapidly evolving field of quantum communication, the regulatory framework plays a crucial role in ensuring security, standardization, and international cooperation. This article examines various approaches employed by countries to regulate quantum communication. The purpose of this research is to comprehensively analyze and compare different international approaches to the regulation of quantum communication to identify key features characteristic of the current stage of development and regulation of quantum communication, as well as to develop recommendations for optimizing and improving regulatory governance in this area. The methodological basis of the study consisted of general scientific and special methods. A detailed study of various legal documents, strategies, and standards related to quantum communication was conducted using the following general scientific methods: analysis, synthesis, induction, and system analysis. Among the special legal methods used was the comparative legal method, which made it possible to identify general trends, differences, and unique approaches in the regulation of quantum communication, as well as the formal-legal method for studying legal categories and legislative techniques used in various acts in the studied area. The study systematically examines legislative measures, government policies, and industry standards to determine the relationship between technological innovation and regulatory governance in the field of quantum communication. The research revealed that the regulation of quantum communication is primarily carried out at the level of strategic documents, such as national roadmaps, which contain recommendations and guidelines for regulating quantum communication. It was found that technical standards play a vital role in the development of quantum communication, with this development occurring at both national and international levels. Special groups and centers have been established for the effective implementation, development, and regulation of quantum communication, which allows for the identification of social, legal, political, and ethical issues. The main conclusions include the need to monitor administrative barriers, identify priority sectors for the implementation of quantum communication, and recognize quantum communication as a dual-use technology. It is recommended that an international certification and tracking system be created for quantum communication devices for export and import control purposes.